-8x+4(x+2x-8)=-12

Simple and best practice solution for -8x+4(x+2x-8)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+4(x+2x-8)=-12 equation:


Simplifying
-8x + 4(x + 2x + -8) = -12

Reorder the terms:
-8x + 4(-8 + x + 2x) = -12

Combine like terms: x + 2x = 3x
-8x + 4(-8 + 3x) = -12
-8x + (-8 * 4 + 3x * 4) = -12
-8x + (-32 + 12x) = -12

Reorder the terms:
-32 + -8x + 12x = -12

Combine like terms: -8x + 12x = 4x
-32 + 4x = -12

Solving
-32 + 4x = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + 4x = -12 + 32

Combine like terms: -32 + 32 = 0
0 + 4x = -12 + 32
4x = -12 + 32

Combine like terms: -12 + 32 = 20
4x = 20

Divide each side by '4'.
x = 5

Simplifying
x = 5

See similar equations:

| 0.4(x-3.5)=5.8x+1.84 | | 5/2a-5=30 | | 3x^8+30x^7+48x^6=0 | | (5-11i)-(-7+5i)= | | 75*60=95*40x | | .5w+5=13 | | (-3)=(-5)-x | | 2x-2[8(x+4)-(x-4)]-2= | | 8h-13-h=4-27h-2 | | 7-12x-5-2x=4 | | 93.96=4.7*p+8.7*p-2.6*p | | (-3)(14)(1.8)= | | 17615+550p=0 | | -42x^2-57x+120=0 | | 6-8(n-5)=6(-8n+2)-6 | | .75k+9=6 | | 11=[m+7] | | (81)^3/4 | | (-4)-x=6 | | (81)^(-3/4) | | 93.96=4.7*p+8.7*p-.6*p | | 3x+6-2x+8=24 | | 4/s–3=-2/5 | | (2x-3)-2(-x+4)=4x-11 | | 4/3y-16=-40 | | N*0.2=25 | | -(-7v+7)-2(v+4)=4v-4v | | 7x-8=8x-9 | | 1.7-11n=-10.7n+2.21 | | 9/5m-10=8 | | x-(-9)=-13 | | 0.7r-6.06=0.3r-13.02 |

Equations solver categories